Faktor yang Mempengaruhi Calon Pengantin Wanita dalam Pelaksanaan Skrining Prakonsepsi di Kua Kecamatan Kuranji - Annisa Sufi Husna; Roza Sri Yanti; Rozi Sastra Purna; Husna Yetti (Jurnal Ventilator, 2026)
The coverage of premarital health services among prospective couples in Indonesia remains low. In 2024, only 39.7% of 1,480,302 registered couples accessed premarital health services. A similar condition was observed in Padang City in 2023, where out of 8,378 registered couples, 7,374 received services, including 180 cases of anemia and 192 undernourished female prospective brides. At Belimbing Community Health Center, preconception service coverage is also suboptimal, with only 54.5% of 774 couples receiving standard services. This study aims to analyze factors influencing the implementation of preconception screening at KUA Kuranji in 2025. This study used an observational analytic design with a cross-sectional approach. Data were collected from 97 respondents. The results showed that knowledge, education, attitudes were significantly associated with preconception screening implementation. Education was identified as the most dominant factor. In conclusion, preconception screening implementation is influenced by both individual and environmental factors. Strengthening health education and improving collaboration between health workers and KUA are essential to enhance participation in preconception screening.